Information in the yield curve: A Macro-Finance approach - Hans Dewachter; Leonardo Iania; Marco Lyrio (National Bank of Belgium, 2014)
We use a macro-finance model, incorporating macroeconomic and financial factors, to study the term premium in the U.S. bond market. Estimating the model using Bayesian techniques, we find that a single factor explains most of the variation in bond risk premiums. Furthermore, the model-implied risk premiums account for up to 40% of the variability of one- and two-year excess returns. Using the model to decompose yield spreads into an expectations and a term premium component, we find that, although this decomposition does not seem important to forecast economic activity, it is crucial to forecast inflation for most forecasting horizons.
Keywords: E43; E44; E47; 330; Macro-finance model; Yield curve; Expectations hypothesis; Rentenmarkt; Zinsstruktur; Erwartungsbildung; Schätzung; Bayes-Statistik; USA